Defining Communicative Competence in Real World Contexts: The European Language Portfolio for Graduates in Business and Management - Šajgalíková, Helena
Nová definícia jazykovej biografie (language biography) absolventov obchodu a manažmentu z pohľadu Európskeho jazykového portfólia - European language portfolio (ELP).